Therapeutics bioconjugates: evaluation of iminoboronates as payload delivery system for cancer - Lopes, Ricardo Miguel Ribeiro Magalhães (2018)
The advent of bioconjugation impacted deeply the world of sciences and technology. New biomolecules were found, biological processes were understood, and novel methodologies were formed due to the fast expansion of this area. The possibility of creating new effective therapies for diseases like cancer is one of big applications of this now big area of study. Off target toxicity was always the problem of potent small molecules with high activity towards specific tumour targets. However, chemotherapy is now selective due to powerful linkers that connect targeting molecules with affinity to interesting biological receptors and cytotoxic drugs. This linkers must have very specific properties, such as high stability in plasma, no toxicity, no interference with ligand affinity nor drug potency, and at the same time, be able to lyse once inside the target molecule to release the therapeutic warhead. Bipolar environments between tumour intracellular and extracellular medias are usually exploited by this linkers in order to complete this goal. The work done in this thesis explores a new model for that same task, specific cancer drug delivery. Iminoboronates were studied due to its remarkable selective stability towards a wide pH range and endogenous molecules. A fluorescence probe was design to validate this model by creating an Off/On system and determine the payload release location in situ. A process was optimized to synthetize the probe 8-(1-aminoethyl)-7-hydroxy-coumarin (1) through a reductive amination reaction in a microwave reactor with 61 % yield. A method to conjugate this probe to ABBA was also optimized, obtaining the iminoboronate in good yields in mild conditions. The iminoboronate model was studied regarding its stability in several simulated biological environments and each half-life time was determined, showing the conjugate is stable most of the cases except in tumour intracellular systems. The construction of folate-ABBA-coumarin bioconjugate have been made to complete this evaluation. The ability to be uptaken by a cancer cell through endocytosis process and the conjugation delivery of coumarin fluorescence payload are two features to hope for in this construct.